Study of an Indirect Injection Diesel Engine Using Pure Coconut Oil, Pure Tamanu Oil and B-20 as Fuel for Smart Microgrid Applications. Part I: Laboratory Testing - Iman Kartolaksono Reksowardojo; Aji Ardiansyah; Tobat Martin Leonardo; Dini Permatasari; Yuli Setyo Indartono; Fariza Almira Ghany (Faculty of Mechanical and Aerospace Engineering, 2023)
Smart Microgrid (SMG) is a hybrid system based on renewable energy which can use biofuel, taking advantage of local resources, as one of its energy sources. This study was conducted to determine the effect of using pure tamanu oil and pure coconut oil on engine performance, emissions, as well as their effects on particular components before and after endurance testing. The experiments were done using a diesel engine at speeds of 2200 rpm. In this study, engine performance and emission tests were done before and after the accelerated endurance tests, with loads of 800 W to 4000 W. The dimensions of the fuel injector nozzle needle and plunger pump were also measured. The fuel performance and emissions results showed slight differences between, before, and after endurance testing. The emissions tests also showed that the two biofuels, especially tamanu, are cleaner than B-20 and have better dimensional measurement results, compared to B-20. Therefore, these biofuels are feasible for replacing B-20, as shown in laboratory testing